-3/4*(-8/7)=
2 2/5*(-7 1/2)=
(-5,2)*4 1/2=
-2,5*(-3,2)
(-4 1/2)*10*3 =
1/4 *(-2)*(-6)*1/12*5=
3*(-1/8)*3/4*(-3 5/9)=
(0,5)*1,2*(-4)*0,1=
3/8:(-5/12)
6/7:(-13/14
(-6 3/4):4 1/2=
(-8 2/5):4 1/2=
(-0,8):(-0,4)=
-6,25:0,25=
-3,5:(-0,5)=
3 3/5:(-0,04)=
- 3 1/4:(0,5)=
(-9):(-4,5)=

2

Odpowiedzi

2010-03-03T17:57:25+01:00
-3/4*(-8/7)= 6/7
2 2/5*(-7 1/2)= 12/5 * (-15/2) = -18
(-5,2)*4 1/2= (-5 1/5) * 9/2 = -26/5 * 9/2 = -117/5 = -23 2/5
-2,5*(-3,2) = -5/2 * (-32/10) = 8
(-4 1/2)*10*3 = -4,5 * 10 * 3 = -45 * 3 = -135
1/4 *(-2)*(-6)*1/12*5= -1/2 * (-6) * 1/12 * 5 = 3/12 * 5 =
= 15/12 = 1 1/4
3*(-1/8)*3/4*(-3 5/9)=-3/8 * 3/4 * (-32/9) = -9/32 * (-32/9) = 1
(0,5)*1,2*(-4)*0,1= 0,6 * (-4) * 0,1 = -2,4 * 0,1 = -0,24
3/8:(-5/12) = 3/8 * (-12/5) = -9/10
6/7:(-13/14) = 6/7 * (-14/13) = -12/13
(-6 3/4):4 1/2= -27/4 : 9/2 = -27/4 * 2/9 = -3/2 = -1 1/2
(-8 2/5):4 1/2= -42/5 : 9/2 = -42/5 * 2/9 = -28/15 = -1 13+15
(-0,8):(-0,4)= -8 : (-4) = 2
-6,25:0,25= -625 : 25 = -25
-3,5:(-0,5)= -35 : (-5) = 7
3 3/5:(-0,04)= 3,6 : (-0,04) = 360 : (-4) = -90
- 3 1/4:(0,5)= -3,25 : 0,5 = -3,25 * 2 = -6,5
(-9):(-4,5)=-90 : (-45) = 2
Najlepsza Odpowiedź!
2010-03-03T18:11:53+01:00
-3/4*(-8/7)=6/7
2 2/5*(-7 1/2)=-18
(-5,2)*4 1/2=-234
-2,5*(-3,2)=40/2
(-4 1/2)*10*3 =-120
1/4 *(-2)*(-6)*1/12*5=5/4
3*(-1/8)*3/4*(-3 5/9)=13/16
(0,5)*1,2*(-4)*0,1=-6/26
3/8:(-5/12)=-9/10
6/7:(-13/14)=-6/12
(-6 3/4):4 1/2=-3
(-8 2/5):4 1/2=-1 13/15
(-0,8):(-0,4)=2
-6,25:0,25=-125
-3,5:(-0,5)=7
3 3/5:(-0,04)=-9
- 3 1/4:(0,5)=-6 1/2
(-9):(-4,5)= 2